The Impact of Small and Medium Enterprises on Gross Domestic Product and Unemployment: Evidence from Jordan 2009-2018 - Al-Afeef, Mohammad Abdel Mohsen (International Journal of Economics and Financial Issues, 2020)
The study aimed to investigate the impact of SMEs funding on, GDP and unemployment, as well as the amount of funding provided by the specialized institutions, and to identify the obstacles that these projects face in obtaining funding. The study population included the SMEs institutions in Jordan between the years 2009 – 2018. The study sample was limited to the Development and Employment Fund in Jordan as one of the most important SMEs funding institutions. Analytical and descriptive method was used to test the hypotheses, the simple regression model used to test the hypotheses of the study through the statistical model (SPSS). The most important finding of this study was the statistically significant impact of financing the SMEs on GDP and unemployment, the study model was able to show 95% of changes in economic development. The study recommended facilitating the provision of financing for SMEs and training the workers in these projects to improve their skills in managing their projects and conducting the appropriate financial analysis for the continuous evaluation of these projects to have positive effects on economic development. The researcher also recommends more analytical studies to reach more accurate results. Keywords: Jordan, Small and Medium Enterprises, Funding, Gross Domestic Product, Unemployment, Development, Financing JEL Classifications: F63; E24; G23 DOI: https://doi.org/10.32479/ijefi.9153